IMPLEMENTASI PROGRAM WISATA EDUKASI DALAM MENUMBUHKAN LITERASI MASYARAKAT DI TAMAN BACA MUTIARA HATI KOTA BUKITTINGGI - Ayu Sri Rejeki; Desriyeni Desriyeni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
This study aims to describe the efforts of Mutiara Hati Reading Park, the implementation of educational tourism programs, and the factors supporting and inhibiting the implementation of educational tourism programs in growing public literacy in Mutiara Hati Reading Park, Bukittinggi City. The sample was conducted by purposive sampling method. Collecting data was conducted by from observations, interviews, and documentation.This data analysis technique was carried out in three steps through data collection, data reduction, and drawing conclusions. The results showed that: (1) the efforts made by Mutiara Hati TBM in fostering community literacy include providing a diverse collection of reading materials, providing comfortable reading rooms, holding interesting programs, documenting all types of activities and uploading them to youtube, in collaboration with the government. and service, providing good service to visitors; (2) the implementation of the educational tourism program to foster community literacy consists of learning English with native speakers, learning to write poetry, short stories, and books, storytelling, learning about plants, visiting kindergartens and elementary schools in Bukittinggi City, watching videos and has been implemented properly discussed in 2 aspects, namely the process and objectives, which include the effects that occur on society and the level of change in society ; (3) supporting factors in implementing educational tourism programs to foster community literacy include support from the Bukittinggi city government, social donations from the Library Service and the Office for the Protection of Women and Children, the existence of reading garden volunteers, support from the local community, the existence of support from literacy activists in the city of Bukittinggi, support from the media or the press, natural conditions and the beauty of a unique reading garden. The inhibiting factors include the uneducational mindset of the community, lack of supporting facilities, the lack of a reading garden volunteer personnel, the location of the reading park on the outskirts of the city, the pandemic situation, the narrow reading park area, the timing of activities that clash with the work schedule and school.